Host Genes Related to Paneth Cells and Xenobiotic Metabolism Are Associated with Shifts in Human Ileum-Associated Microbial Composition - Zhang, Tianyi; DeSimone, Robert A.; Jiao, Xiangmin; Rohlf, F. James; Zhu, Wei; Gong, Qing Qing; Hunt, Steven R.; Dassopoulos, Themistocles; Newberry, Rodney D.; Sodergren, Erica; Weinstock, George; Robertson, Charles E.; et al. (PLOS ONE, 2012)
The aim of this study was to integrate human clinical, genotype, mRNA microarray and 16 S rRNA sequence data collected on 84 subjects with ileal Crohn’s disease, ulcerative colitis or control patients without inflammatory bowel diseases in order to interrogate how host-microbial interactions are perturbed in inflammatory bowel diseases (IBD). Ex-vivo ileal mucosal biopsies were collected from the disease unaffected proximal margin of the ileum resected from patients who were undergoing initial intestinal surgery. Both RNA and DNA were extracted from the mucosal biopsy samples. Patients were genotyped for the three major NOD2 variants (Leufs1007, R702W, and G908R) and the ATG16L1T300A variant. Whole human genome mRNA expression profiles were generated using Agilent microarrays. Microbial composition profiles were determined by 454 pyrosequencing of the V3–V5 hypervariable region of the bacterial 16 S rRNA gene. The results of permutation based multivariate analysis of variance and covariance (MANCOVA) support the hypothesis that host mucosal Paneth cell and xenobiotic metabolism genes play an important role in host microbial interactions.